Forging India Germany Partnerships in Skills Development - (:unkn) unknown (My University, 2013)
Cooperation between Germany and India in vocational education and training (VET) is developing at a rapid pace. It advanced to a new level when Germany's Federal Minister of Education Schavan signed a 'Memorandum of Understanding' (MoU) on cooperation in the VET field on 31 May 2011 during German-Indian government consultations in New Delhi. Prior to that, in October 2010, BIBB & iMOVE at BIBB signed a cooperation agreement with the Federation of Indian Chambers of Commerce and Industry (FICCI). This agreement provides for regular exchanges in numerous areas of VET such as the development of occupational standards, the provision of training for instruction personnel and the establishment of contacts between initial and continuing training providers and enterprises. The Indo-German Joint Working Group on VET, which was constituted in 2007, was entrusted with the task of conducting and monitoring the activities mentioned in the MoU. This publication shows how the Indo-German Partnership in VET has developed over the course of time. It not only captures the spirit of partnerships in skills development but also the areas that have evolved and need further nurturing for promoting trade and bilateral investments. Several examples of joint projects, including skills development projects of MoL&E (Ministry of Labour & Employment) with German partners and projects whith National Skill Development Council (NSDC) partners are doing with German stakeholders are presented. (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 2.1 Deutschland; I 2.3.4 Asien; Berufsbildung; Internationale Zusammenarbeit; Bundesrepublik Deutschland; Indien